TEOREMA TITIK TETAP BANACH PADA RUANG METRIK-D - Muhammad Ahsar Karim; Dewi Sri Susanti; Nurul Huda (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2010)
In the space of metrics known the fixed point theorem of Banach. In this paper, the theorem will be constructed in the D-metric space. This study begins with construction concepts: open ball, open set, convergent lines, and Cauchy rows respectively in the D-metric space. Then given the concept of continuous mapping and mapping continuous uniform in the D-metric space. Further constructed Banach's fixed point theorem at in the D-metric space.